Efficacy of Serum Levels of Antioxidants in Oral Submucous Fibrosis Patients - Satyam Joshi; Khushboo Desai; Hemal Joshi; Darshan Patel; Neha Verma; Riya Shah (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background and Aim: Serum total protein, albumin and uric acid are plasma’s potent antioxidant defense; it comes out convincing enough to be used as a reliable marker of oxidative stress in the body and could be helpful in the early identification of oral submucous fibrosis (OSMF), against the other invasive and not so cost effective diagnostic adjuncts. Hence the present study was aimed to compare the serum levels of total protein, albumin and uric acid in oral submucous fibrosis patients.Material & Methods: Patients were assigned to one of three groups: Group one consisted of 25 healthy individuals, Group two consisted of 25 individuals with chewing tobacco habit without OSMF, Group three consisted of 25 patients with chewing tobacco habit with OSMF. Participants were instructed to fast overnight. On the following day between 8 and 10 AM, 5 ml of venous blood was drawn from each subject using a sterile disposable syringe taking care to prevent hemolysis. Assay of albumin & total protein were carried out using the bromocresol green method and that for uric acid was carried out by biuret method.Results: Mean serum levels of Total protein decreased from group I to group III; difference was not found to be statistically significant. Serum levels of Albumin decreased from group I to group III; difference was found to be statistically significant (p < 0.05). Serum levels of Uric acid decreased from group I to group II; difference was found to be statistically significant (p < 0.05).Conclusion: Our findings suggest that the degree of oxidative damage in OSMF can be assessed by estimation of serum Total Protein, Albumin & Uric Acid levels in affected patients. Underlying deficiency of antioxidants can be corrected by dietary supplementation of these antioxidants. This may be helpful for successful management of OSMF and for avoiding the consequences of malignancy.